2007
DOI: 10.1103/physrevd.75.014506
|View full text |Cite
|
Sign up to set email alerts
|

Quarkonium correlators and spectral functions at zero and finite temperature

Abstract: We study quarkonium correlators and spectral functions at zero and finite temperature using the anisotropic Fermilab lattice formulation with anisotropy ξ = 2 and 4. To control cutoff effects we use several different lattice spacings. The spectral functions were extracted from lattice correlators with Maximum Entropy Method based on a new algorithm. We find evidence for the survival of 1S quarkonium states in the deconfined medium till relatively high temperatures as well as for dissolution of 1P quarkonium st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
404
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(443 citation statements)
references
References 58 publications
35
404
4
Order By: Relevance
“…Also shown in Fig.1 is the spectral function in the scalar channel from Ref. [13]. The 1st peak corresponds to χ c0 (1P ) state.…”
Section: Charmonia Correlators and Spectral Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also shown in Fig.1 is the spectral function in the scalar channel from Ref. [13]. The 1st peak corresponds to χ c0 (1P ) state.…”
Section: Charmonia Correlators and Spectral Functionsmentioning
confidence: 99%
“…Lattice calculation of charmonium spectral functions appeared recently and suggested, contrary to potential models, that J/ψ and η c survive at temperatures as high as 1.6T c [9,10,11,12]. It has been also found that χ c melts at temperature of about 1.1T c [11,12,13]. There are also preliminary calculations of the bottomonium spectral functions [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations